Continuing education of science teachers: an analysis in scientific journals - Rocha, Thaís Rios da (2020)
This work presents the results of a bibliographic research carried out in order to investigate how the continuing education courses for science teachers in basic education are organized at national and international levels. Ten journals were selected for analysis from 2006 to 2016, 6 national and 4 international. After an exploratory, analytical and interpretative reading of the 68 selected articles, emergent categories appeared according to the similarities of the subjects covered in the formation courses. The articles were also analyzed regarding the scope, type of formation, level of performance of the participating teachers and duration of the courses. Among the results, we found that only 13 of the 68 articles describe continuing education activities carried out for basic and secondary education science teachers, which highlights the lack of this type of formation for teachers in the basic education network.